2021
DOI: 10.1037/rep0000391
|View full text |Cite
|
Sign up to set email alerts
|

Coping with stigmatization and discrimination related to blindness and low vision.

Abstract: Purpose/Objective: Research suggests that effective coping with stress related to stigmatization and discrimination might protect the stigmatized persons against poor mental health outcomes associated with experiencing stress. Despite this, research specifically on coping with social stigma among people who are blind or have low vision has received less attention. We addressed this gap in the literature, by exploring the lived experiences of people who are blind or have low vision with regard to their percepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 60 publications
1
1
0
Order By: Relevance
“…The multitude of coping strategies developed by PWAs directly echoes the fact that they must constantly adapt to societal norms in order to be perceived as “normal.” Some have such an urgent need to conform that they go to great lengths to conceal their disability, which may exhaust them. Another recent study has obtained similar results in patients with visual impairments (VI) [ 84 ].…”
Section: Discussionsupporting
confidence: 61%
“…The multitude of coping strategies developed by PWAs directly echoes the fact that they must constantly adapt to societal norms in order to be perceived as “normal.” Some have such an urgent need to conform that they go to great lengths to conceal their disability, which may exhaust them. Another recent study has obtained similar results in patients with visual impairments (VI) [ 84 ].…”
Section: Discussionsupporting
confidence: 61%
“…This type of behavior requires considerable effort from the person who gradually becomes exhausted and therefore weakens. Other studies revealed similar results in patients with intellectual disabilities [187,188] and visual impairments [189]. Indeed, depending on the degree to which their impairment is mild or severe, people with physical or sensory impairments might attempt to overcome their difficulties in order to be considered as "normal" [136].…”
Section: Discussionmentioning
confidence: 79%
“…Because stigma is something that individuals with disabilities routinely carry with them as they participate in daily life, work, and other activities 17) , it is conceivable that individuals with visual impairments experienced more stress during the pandemic than they did in their daily lives. Like them, others in the community felt various stigmas in complying with infection control measures, so it can be assumed that there were difficulties in responding in a tolerant manner, even though they felt that contact and voice were necessary support for those with visual impairments.…”
Section: Discussionmentioning
confidence: 99%